Group-arrange-touch-up (GAT): a method of teaching non-native Mandarin speakers in restructuring elementary Mandarin sentence / Hoe Foo Terng and Mah Boon Yih - Hoe, Foo Terng; Mah, Boon Yih (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2011)
In Malaysian local universities, Mandarin is offered as the third language course to students who are the non-native Mandarin speakers. Since Mandarin is distinctive with Its own grammatical and sentence patterns, Mandarin Instructors need to come up with the effective method to teach the non-native speakers who are rather weak In restructuring Mandarin sentences. Many non-native speakers of Mandarin are fall to restructure Mandarin sentences correctly at elementary level due to the limited contact hours, unsupportlve Mandarin learning environment, and the Influence of mother tongue. To reduce this learning predicament among these non-native speakers, this paper proposes the use of GAT method for restructuring Mandarin sentences. GAT, an acronym for Group-Arrange-Touch-up, Incorporates Word Sequence'Diagram (WSD) In the form of graphic Impressions, which can be used by non-native speakers In their quest of learning Mandarin. This method Is supported by the 'word sequence' approach and other relevant theories proposed by some prominent researchers such as Liu Hongmo, Shen Xlaolong, and Zhang Llzhao. This paper demonstrates how GAT Is used to teach non-native speakers to restructure basic Mandarin sentences without the need to master the grammar of Mandarin thoroughly. After Implementing GAT In a Mandarin class throughout a four-month semester In Unlversltl Teknologi MARA (UITM) Penang Campus, the result obtained from an oral Interview to the students had found that GAT was a favourable method among the Malay students In restructuring Mandarin sentences.